Stability analysis of roadside backfill body at gob-side entry retaining under combined static and dynamic loading. (September 2021) - Meng, Ningkang; Bai, Jianbiao; Chen, Yong; Wang, Xiangyu; Wu, Wenda; Wu, Bowen
Highlights: The effect of cutting angles on RBB was discussed under static and dynamic loading. Static loading is a bigger contributor to the failure compared to dynamic loading. A combined support measure is proposed. Abstract: The applications of gob-side entry retaining (GER) techniques tends to increase over time as it can increase the minerals recovery rate and reduce the output of the waste. In the literature, only the performance of the roadside backfill body (RBB) at gob-side entry retaining under static loading has been investigated. However, failure mechanisms of the RBB under dynamic loading with various roof cutting angles have not been addressed. This study presented an numerical simulation of the fracture propagation and distribution in the roadside backfill body along the gob-side under combined static and dynamic loadings using the Trigon model built in UDEC (Discrete element methods) software. The influence of the roof cutting angles on the behavior of the RBB was also discussed. The input parameters were determined by back analysis with the field data. Results of the model show that static loading is a bigger contributor to the failure of the RBB compared to the dynamic loading. Several clear fractures were observed at top left and bottom right of the RBB and the fracture was more intensive at top left. In addition, it was found that if the roof cutting angle is 70°, the influence of the dynamic loading on the RBB is minimum, and the area and severity of the shearing failure in the RBB is minimum as well. As a result, it was determined the optimal roof cutting angle was 70° and a combined support measure of "roof cutting + roof support above RBBs + RBB reinforcement" is proposed. The application of roof cutting in gob-side entry retaining (RCGER) techniques in the Lingzhida coal mine indicates that deformation of the surrounding rocks can be effectively controlled.